2000
DOI: 10.1111/j.1749-6632.2000.tb06764.x
|View full text |Cite
|
Sign up to set email alerts
|

The First Discovery of the Gas Hydrates in the Sediments of the Lake Baikal

Abstract: In 1997 an underwater borehole was drilled in the South part of Lake Baikal (water depth, 1,433 m; borehole depth, 225 m; the temperature at these depths is about 10°C). Samples of sediments containing methane hydrate were collected at depths 121 and 161 m below bottom. At present, this is the only example of the existence of gas hydrates in a fresh‐water basin under non‐permafrost conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 1 publication
1
13
0
1
Order By: Relevance
“…The possibility of GH occurrence in Baikal sediments was suggested as early as 1980 [2]; later, a BSR seismic reflector was discovered in the course of multichannel seismic survey [3]. The first GH samples were lifted in 1997 from depths of 121 and 161 m with the core of Hole BDP-97, which was drilled in the Southern Basin of Baikal [4].…”
Section: Introductionmentioning
confidence: 99%
“…The possibility of GH occurrence in Baikal sediments was suggested as early as 1980 [2]; later, a BSR seismic reflector was discovered in the course of multichannel seismic survey [3]. The first GH samples were lifted in 1997 from depths of 121 and 161 m with the core of Hole BDP-97, which was drilled in the Southern Basin of Baikal [4].…”
Section: Introductionmentioning
confidence: 99%
“…Vanneste et al (2001) roughly estimated from seismic surveys that the total amount of CH 4 stored as hydrates in the sediments could be as high as 6 Pg. Based on its carbon isotopic composition, it has been suggested that the CH 4 in hydrates from the South Basin may be of biogenic origin (Kuzmin et al 2000), whereas recent observations indicate also a thermogenic component in hydrates collected in the Central Basin (Kida et al 2006). CH 4 is locally released by gas seeps and mud volcanoes (Fig.…”
mentioning
confidence: 99%
“…Besides the Black Sea (Vassilev and Dimitrov 2002), Lake Baikal is the only inland water mass in which large amounts of methane hydrates have been observed in the sediment (Hutchinson et al 1991;Golmshtok et al 1997;Kuzmin et al 2000) (Fig. 1).…”
mentioning
confidence: 99%
“…Cores show biogenic gas hydrates with gas compositions approaching 99% methane (de Batist et al, 2002;Kuzmin et al, 2000), while seismic data show that BGHS extends 300-350 m below the floor of the lake. Cores show biogenic gas hydrates with gas compositions approaching 99% methane (de Batist et al, 2002;Kuzmin et al, 2000), while seismic data show that BGHS extends 300-350 m below the floor of the lake.…”
Section: Mud Volcanism In the Freshwater Of Lake Baikalmentioning
confidence: 99%